Resource characteristics and stock assessment of whitebaits - Luther, G; Rao, K V Narayana; Gopakumar, G; Muthiah, C; Pillai, N Gopalakrishna; Rohith, Prathibha; Kurup, K Narayana; Reuben, S; Devadoss, P; Rao, G Syda; Bennet, P Sam; Radhakrishnan, N S (Indian Journal of Fisheries, 2011)
The fishery of whitebait for 1979-88 was studied. The southern maritime states accounted for 97% of thecountry's whitebait landings. The quartelWise whitebait landings, gearwise catch and catch per unit effort for1985-88 were studied and discussed. Encrasicholina devisi and Stolephoru., waitei were the dominant speciesin the whitebait fishery. The fishery and biological characteristics of these two species at Visakhapatnam,Madras, Vizhinjam, Cochin and Mangalore are presented. Whitebait are short-lived fish, the longevity of E.devisi being 1.9 years and that of S. waite; about 2.3 years. Both the species get recruited into the fishing groundat about 30-35 mrn total length when 2-3 months old. The fish from 40-55 mm length onwards (3-5 months old)are caught in greater abundance. The major bulk of the annuallalldings is constituted by 6-15 months old fish.The growth parameters, mortality rates and exploitation ratios of the two species were estimated for both thecoasts. Critical evaluation of the maximum sustainable yield (MSY) estimates in relation to biomass at MSYlevel indicilted the possible increase in production of E. devi.fi by about 20% over the current yield with highereffort input along the west coast. For E. devi.,i in the east coast and S. waitei in both the coasts, the expectedincrease was only marginal.